The Correlation Between Students Habit of Listening to English Songs and Their Listening Comprehension Skills of Second Semester Students at Universitas Bhinneka PGRI - Larasati, Nurjihan Widya; Hanafi, Moh. (English Education and Literature Journal (E-Jou), 2025)
This study explores how frequently students listen to English songs and how it influences their ability to understand spoken language. The participants were second-semester students from the English Education Study Program at Universitas Bhinneka PGRI and applied a correlational quantitative approach. Data were gathered using two instruments: a structured questionnaire to measure students’ listening habits and a standardized listening comprehension test. A total of 21 students participated as respondents through a total sampling approach. Statistical analysis was conducted using the Pearson Product-Moment correlation formula. The results revealed a strong and statistically significant relationship between the frequency of listening to English songs and students' listening test scores (r = 0.981; p < 0.05). This suggests that students who regularly listen to English songs tend to demonstrate higher comprehension abilities. These findings support the acceptance of the study’s hypothesis. The research highlights the pedagogical potential of integrating music-based input into language learning and opens avenues for further exploration on how informal listening practices contribute to language development among EFL learners.